Utilization and barriers of inclusive education resource centers: The case of Gamo zone primary schools - Tsega, Sewalem; Sapo, Solomon (Bahir Dar Journal of Education, 2024)
This study aimed to examine teachers’ utilization of Inclusive Education resource centers and identify the barriers that hinder the function of the centers in primary schools of Gamo Zone. For this purpose, the study employed a mixed methods explanatory sequential design. Primary data were collected from 95 teachers and 41 members of Resource Center Core Teams. Self-developed questionnaires, semi-structured interviews, and document analysis were used to gather data. Quantitative data analysis involved the use of percentage, mean, standard deviation, and independent sample t-tests, while qualitative data was analyzed through narrative and descriptive techniques. Results revealed that teachers did not adequately utilize the centers. Moreover, barriers such as shortage of specialized staff, inadequate training, lack of specialist support, limited resources, absence of qualified personnel, insufficient monitoring tools for students with special needs, and inadequate funding were identified. Finally, measures that aimed to enhance teachers’ utilization of the centers and address the barriers identified are forwarded.